Catalytic Synthesis of Riboside–Amino Acid Hybrids - Ochocińska, Agata M.; Bethel, Paul A.; Sweeney, Joseph B. (Synlett, 2013)
The catalytic synthesis of 3-(2′-glycinoyl)ribose derivatives under mild conditions is described. The key reaction involves silver-catalyzed condensation of isocyanoacetates with 3-ketoriboses.
Keywords: catalytic; non-coded amino acids; hybrid peptides; ribonucleoproteins; asymmetric synthesis